2016
DOI: 10.1038/srep27664
|View full text |Cite
|
Sign up to set email alerts
|

Reduced anticipation of negative emotional events in alexithymia

Abstract: Alexithymia is characterized by difficulties in different domains of emotion processing, especially in relation to negative emotions. Nevertheless, its causal mechanisms remain elusive. Reduced anticipation of negative emotional events might be one such mechanism because it enables the individual to prepare to respond effectively to coming events. To test this, changes in skin conductance response (SCR) were recorded during classical fear conditioning in sixty participants with high (HA), medium (MA) and low (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 70 publications
(94 reference statements)
2
15
0
Order By: Relevance
“…In line with this, we have previously proposed a different account of alexithymia and argued that alexithymia may be understood as impairment in effectively learning the emotional value of encountered stimuli, and showed that individuals with alexithymia have reduced psychophysiological response to aversively conditioned stimuli during Pavlovian threat conditioning, despite preserved response to unconditioned stimuli (Starita et al, 2016). Therefore, individuals with alexithymia appear able to respond to stimuli, which are biologically prepared to trigger an emotional response.…”
Section: Introductionmentioning
confidence: 80%
“…In line with this, we have previously proposed a different account of alexithymia and argued that alexithymia may be understood as impairment in effectively learning the emotional value of encountered stimuli, and showed that individuals with alexithymia have reduced psychophysiological response to aversively conditioned stimuli during Pavlovian threat conditioning, despite preserved response to unconditioned stimuli (Starita et al, 2016). Therefore, individuals with alexithymia appear able to respond to stimuli, which are biologically prepared to trigger an emotional response.…”
Section: Introductionmentioning
confidence: 80%
“…In addition, HA show impairment in embodied aspects of fearful stimuli processing. This is evidenced by reduced rapid facial mimicry in response to static fearful faces ( Sonnby-Borgstrom, 2009 ; Scarpazza et al, 2018 ), failure to show enhanced perception of tactile stimuli delivered to their face while observing a fearful – as opposed to happy or neutral – face being simultaneously touched ( Scarpazza et al, 2014 , 2015 ) and reduced skin conductance response when viewing a conditioned stimulus predictive of a shock during classical fear conditioning ( Starita et al, 2016 ). Finally, HA show impairments in processing fearful stimuli also when examining their electrophysiological responses.…”
Section: Discussionmentioning
confidence: 99%
“…The dissociation between embodiment of fearful and happy facial expressions in HA is in accordance with the previous research suggesting that HA participants mainly experience a difficulty in processing negative emotions. Individuals with high alexithymia show altered responses to many types of negative stimuli, such as early auditoryrelated potentials in response to potentially dangerous acoustic stimuli (Schäfer et al 2007), reduced electrodermal responses to negative pictures (Pollatos et al 2008), impaired internal somatic simulation of fearful faces (Scarpazza et al 2014), and decreased anticipation of the occurrence of a negative emotional event (Starita et al 2016). On the other hand, an important body of the literature suggested that processing of positive emotions is spared in HA (see for instance: Borhani et al 2016;Maier et al 2016;SonnbyBorgstrom 2009;Pollatos et al 2008).…”
Section: Discussionmentioning
confidence: 99%